Age-Related Pathways in Cardiac Regeneration: A Role for lncRNAs? - Santos, Francisco; Correia, Magda; Nóbrega-Pereira, Sandrina; Bernardes de Jesus, Bruno (Frontiers in Physiology, 2021)
Aging imposes a barrier for tissue regeneration. In the heart, aging leads to a severe rearrangement of the cardiac structure and function and to a subsequent increased risk of heart failure. An intricate network of distinct pathways contributes to age-related alterations during healthy heart aging and account for the higher susceptibility of heart disease. Our understanding of the systemic aging process has already leaded to the design of anti-aging strategies or to the adoption of protective interventions such has the cardioprotective role of exercise. Still, our understanding of the molecular determinants operating during cardiac aging or repair remains limited. Here, we will recapitulate the molecular and physiological alterations operating during heart aging, highlighting the potential role for long non-coding RNAs (lncRNAs) as novel and valuable targets in cardiac regeneration/repair.